An Analysis of the Determinants of Corporate Social Responsibility of Brazilian Firms - Vicente Lima Crisóstomo; Maria Rafaela Oliveira (BBR: Brazilian Business Review)
This work makes an analysis of the determinants of Corporate Social Responsibility (CSR) of Brazilian firms, as proxied by firm membership of the ISE Index of BM&FBOVESPA. Besides other proposed determinants of CSR present in the literature (firm size, profitability, growth opportunities), the work examines ownership concentration and the persistence on CSR status. Logit regression estimates have been run for a sample of 1649 firm-year observations in the period 2006-2011. The findings show that CSR of Brazilian firms is inversely correlated to its ownership concentration indicating that controlling voting shareholders may not see social concerns as a priority. Besides, firms tend to maintain their present CSR status. The results also indicate that leading CSR firms are larger, face more growth opportunities, and are persistent in their superior CSR situation.